A Reconfiguration Algorithm for the Single-Driven Hexapod-Type Parallel Mechanism - Fomin, Alexey; Antonov, Anton; Glazunov, Victor (Robotics (Basel), 2022)
This paper presents a hexapod-type reconfigurable parallel mechanism that operates from a single actuator. The mechanism design allows reproducing diverse output link trajectories without using additional actuators. The paper provides the kinematic analysis where the analytical relationships between the output link coordinates and actuated movement are determined. These relations are used next to develop an original and computationally effective algorithm for the reconfiguration procedure. The algorithm enables selecting mechanism parameters to realize a specific output link trajectory. Several examples demonstrate the implementation of the proposed techniques. CAD simulations on a mechanism virtual prototype verify the correctness of the suggested algorithm.